COMBEAMS: A numerical tool for the structural verification of steel-concrete composite beamsgit - Jorge Palomino Tamayo; Lucas Alves de Aguiar; Cristian de Campos; Daniel Barbosa Mapurunga Matos; Inácio Benvegnu Morsch (SoftwareX)
This paper presents a computer program named COMBEAMS written in Python and intended for the design verification of continuous steel-concrete composite beams under the ultimate limit state. Due to its friendly graphical interface the program allows the user to interact with the output results expressed in terms of computed shear and bending moment diagrams as well as computed shear connector distribution along the steel-concrete interface. Particularly, this last issue is important as connectors transfer the shear flow from the concrete slab to the steel profile to guarantee the desirable interaction between both members. The program can be also inserted into other methodologies. This tool will certainly aim engineers and researchers with their daily tasks.